Synthesis of Silver Nanoparticles Using Premna serratifolia Linn. Leaf Extract as Reducing Agent and Their Antibacterial Activity - Chris Octavianus; Imelda Hotmarisi Silalahi; Gusrizal Gusrizal (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2022)
Premna serratifolia Linn. leaf extract has been used as a reducing agent in the synthesis of silver nanoparticles (AgNPs). Various synthesis parameters such as reaction time, concentration and the pH of the Premna serratifolia Linn. leaf extract, and silver nitrate concentration were investigated. In addition, the stability of synthesized AgNPs and their activity against Staphylococcus aureus and Escherichia coli have also been investigated. The results of the experiment showed that Premna serratifolia Linn. leaf extract reduced silver ions resulting in AgNPs. In addition, the AgNPs colloid showed a gradual change in color from transparent green to yellow. At the same time, its ultraviolet (UV)-Visible spectra exhibited the typical surface plasmon resonance peak at around 400-415 nm. The optimum reaction conditions in the formation of AgNPs are 40 minutes of reaction time using silver nitrate 1.5x10-4 M and Premna serratifolia Linn leaf extract 80 ppm at pH 10. The particle size of synthesized AgNPs distributes from 48.3-157 nm with an average size of 58.7±14.4 nm and is stable at least for 1-month storage under ambient conditions. The antibacterial test shows that synthesized AgNPs are effective against both Escherichia coli and Staphylococcus aureus.